Jejak Peninggalan Kapiten Lie Eng Tjie Di Kampung Baru, Singaraja Sebagai Sumber Belajar Sejarah Di SMA - Putra, Komang Yoga Laksana Kusuma Putra; Pageh, I Made Pageh; Arta, Ketut Sedana Arta (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This study aims to: (1) find out the remaining traces of historical relics from Captain Lie Eng Tjie in Kampung Baru Village, Singaraja, Bali; (2) find out the function of historical relics from Captain Lei Eng Tjie in Kampung Baru Village, Singaraja, Bali; (3) what aspects of historical relics from Captain Lei Eng Tjie can be used as learning resources in high school. This study was located in Kampung Baru Village, Singaraja, Buleleng Regency, Bali, using historical research methods consisting of: heuristics (document studies, observation and interviews), source criticism (internal and external), interpretation and historiography. The results of this study indicate: (1) the traces of the relics of Captain Lie Eng Tjie in Kampung Baru Village, Singaraja, Buleleng, Bali cannot be separated from the background of the arrival of ethnic Chinese to Indonesia due to political and economic turmoil in China, Captain Lie Eng Tjie came to Bali via trade routes and settled in Singaraja, thanks to his influence and wealth, he was appointed as Captain by the Dutch colonial government in the early 20th century. (2) Traces of Captain Lie Eng Tjie still remain in the form of: houses, altars of worship, statues of Chinese gods, and the tomb of Captain Lie Eng Tjie as symbols of Chinese culture, spirituality, and identity in North Bali. His house and temple reflect the Chinese-Balinese acculturation which became the center of religious and social activities. (3) The legacy of Captain Lie Eng Tjie has high religious, social, historical and knowledge values ​​and reflects tolerance and diversity. This Chinese legacy is in line with the Merdeka Curriculum, so it can be optimized in history learning in SMA in phase E in achieving local history learning. Keywords: traces of legacy, Captain Lie Eng Tjie, learning resources